Cuantificación de las concentraciones de metales pesados (Hg, Cu,Ni , Zn, Cd, Pb y Mn) por espectrofotometría de absorción atómica en peces del estero Huaylá (Diapterus peruvianuns Sardinops sagax), Puerto Bolivar, cantón Machala, provincia de El Oro, 2014. - Ortega Pereira, Carolina Lissette (2015)
The objective of this research was to quantify Mercury, Copper, Nickel, Zinc, Cadmium, Lead and Manganese by atomic absorption spectrophotometry, fish (Sardinops sagax and Diapterus peruvianus) that inhabit the estuary of the parish Huayla Puerto Bolivar. Fish were caught in the two species studied in the case of the squat in in three sizes small, medium and large and sardines in size small, size made notes. 0.5 grams of dried tissue was weighed is added a 3, 1 mixture of nitric and perchloric acid to remove the entire contents of trace metals placed on a heating plate and sand bath at 70 C for two hours and then the residue afora filtrate to 100 mL.